La religion à l'école Négociations autour de la présence publique des communautés religieuses - Rota, Andrea (Seismo, 2017)
In the last few decades, the organization of religious education classes in Swiss public school has been the object of profound public scrutiny. In the wake of these debates, most cantons have introduced a new course under the responsibility of the State in which a plurality of religions is presented. The attribution of this new competence to the State has prompted the reaction of various religious communities and has stimulated, within these communities, a reflection on their social role. Drawing on forty in-depth interviews with representatives of different religious communities, this study analyzes the strategies used by religious actors to position themselves in the public sphere. Against this backdrop, the study discusses the evolution of the relationships between religious communities and society and puts forward new perspectives in the sociological debate on the public presence of religion.